PENGARUH SANKSI PERPAJAKAN, LINGKUNGAN WAJIB PAJAK DAN RASIONALITAS WAJIB PAJAK PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN PREFERENSI RISIKO SEBAGAI MODERASI (STUDI KASUS WAJIB PAJAK DAERAH WONOCOLO, SURABAYA) - Achmad In’am Munhamir; Niken Savitri Primasari (Bajang Institute, 2022)
Taxes are the main source of state finances in Indonesia that are used as much as possible for the welfare of the general public. The role of taxes is very large for the cost of development and the country's economy. The Directorate General of Taxes has tried various ways to maximize tax revenues. One of the efforts made is the enactment of a self-assessment system in collecting taxes, especially with the existence of digital technology that makes it easier for people to do initiative and awareness in reporting their taxes. This system gives confidence and responsibility to taxpayers to take the initiative to take care of their own tax affairs. The results of the data and statistics concluded that tax sanctions, tax environment and tax rationality without moderation strongly affect positively and significantly with compliance. But when moderation is done, only variable tax sanctions can affect the compliance of taxpayers